Antimicrobial susceptibility of Vibrio vulnificus and Vibrio parahaemolyticus recovered from recreational and commercial areas of Chesapeake Bay and Maryland Coastal Bays. - Kristi S Shaw; Rachel E Rosenberg Goldstein; Xin He; John M Jacobs; Byron C Crump; Amy R Sapkota (PLoS ONE)
Vibrio vulnificus and V. parahaemolyticus in the estuarine-marine environment are of human health significance and may be increasing in pathogenicity and abundance. Vibrio illness originating from dermal contact with Vibrio laden waters or through ingestion of seafood originating from such waters can cause deleterious health effects, particularly if the strains involved are resistant to clinically important antibiotics. The purpose of this study was to evaluate antimicrobial susceptibility among these pathogens. Surface-water samples were collected from three sites of recreational and commercial importance from July to September 2009. Samples were plated onto species-specific media and resulting V. vulnificus and V. parahaemolyticus strains were confirmed using polymerase chain reaction assays and tested for antimicrobial susceptibility using the Sensititre® microbroth dilution system. Descriptive statistics, Friedman two-way Analysis of Variance (ANOVA) and Kruskal-Wallis one-way ANOVA were used to analyze the data. Vibrio vulnificus (n = 120) and V. parahaemolyticus (n = 77) were isolated from all sampling sites. Most isolates were susceptible to antibiotics recommended for treating Vibrio infections, although the majority of isolates expressed intermediate resistance to chloramphenicol (78% of V. vulnificus, 96% of V. parahaemolyticus). Vibrio parahaemolyticus also demonstrated resistance to penicillin (68%). Sampling location or month did not significantly impact V. parahaemolyticus resistance patterns, but V. vulnificus isolates from St. Martin's River had lower overall intermediate resistance than that of the other two sampling sites during the month of July (p = 0.0166). Antibiotics recommended to treat adult Vibrio infections were effective in suppressing bacterial growth, while some antibiotics recommended for pediatric treatment were not effective against some of the recovered isolates. To our knowledge, these are the first antimicrobial susceptibility data of V. vulnificus and V. parahaemolyticus recovered from the Chesapeake Bay. These data can serve as a baseline against which future studies can be compared to evaluate whether susceptibilities change over time.